2021
DOI: 10.1177/15280837211051951
|View full text |Cite
|
Sign up to set email alerts
|

Mouldability analysis and impact performance of 3D aramid angle-interlock fabric panels for ballistic helmets

Abstract: Modern ballistic helmets made from textile composites offer enhanced protection with lightweight, but the discontinuity of the reinforcing materials is a potential problem affecting the helmet performance. This work uses 3D angle-interlock fabrics to provide reinforcement continuity, and evaluates 3D through-the-thickness angle-interlock (TTAI) fabrics to study the influence of fabric structural parameters on fabric mouldabilty and ballistic performance for ballistic helmet application. The mouldability was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, it was found that because the metal z-filaments can sustain higher plastic deformation than their carbon counterpart, they are less effective than carbon z-filaments at increasing fatigue resistance under both mode I and mode II loadings [20]. Meanwhile, researchers also simulated the damage form of composites with 3D structures through various analysis models to predict the mechanical properties of composites [21][22][23][24]. However, there is currently limited research on the 3D preform structure design.…”
mentioning
confidence: 99%
“…In addition, it was found that because the metal z-filaments can sustain higher plastic deformation than their carbon counterpart, they are less effective than carbon z-filaments at increasing fatigue resistance under both mode I and mode II loadings [20]. Meanwhile, researchers also simulated the damage form of composites with 3D structures through various analysis models to predict the mechanical properties of composites [21][22][23][24]. However, there is currently limited research on the 3D preform structure design.…”
mentioning
confidence: 99%